Validation of Dimensions of Learning Organization Questionnaire (DLOQ) in health care setting in Greece - Aspasia Goula; Maria-Aggeliki Stamouli; Dimitra Latsou; Vasiliki Gkioka; Markos Sarris (SAGE Publishing, 2020)
Background: In health care systems the organizational learning is a continuous process to improve actions through better knowledge and detect or correct errors. This study examines the validity and reliability of the Dimensions of Learning Organization Questionnaire in addition to the applicability of the instrument in a Greek health care cultural context. Design and methods: Α cross-sectional study was carried out in 6 general hospitals of Attica and the sampling scheme was the stratified sampling. Questionnaires were distributed to 487 healthcare professionals and 380 valid questionnaires were returned. The research tool used in this survey is the extensive form of DLOQ, which has been adapted and translated into Greek language. Data analysis was carried out with SPSS 25. Results: Three leading experts of the health sector examined the face validity assessment of the translated DLOQ and stated that it is characterized by high face validity. As regard construct validity of the DOLQ throughout Multitrait-Multimethod Matrix, was proved that all the variables of the same factors are statistically significantly correlated (p<0.001), and their correlation coefficients have moderate to high power ranging between 0.563 and 0.798. Moreover, the discriminant validity was demonstrated as certain correlation coefficients between variables of different factors were found to be higher than of certain correlation coefficients between variables of the same factors. The internal consistency among the items of the DOLQ range between 0.842 and 0.977 and they are considered to be good to excellent. Conclusions: Our results confirmed that DLOQ is a valuable tool in measuring Learning Organizational in Greek public hospitals.